Synthesis of N-Doped Graphene Photo-Catalyst for Photo-Assisted Charging of Li-Ion Oxygen Battery - Kacar, Nilay; Lokcu, Ersu; Cayirli, Meltem; Ozden, Resat Can; Coskun, Sahin; Toparli, Cigdem; Anik, Mustafa (Wiley-V C H Verlag Gmbh, 2024)
In this work, nitrogen (N)-doped graphene film is synthesized, as a photo-catalyst, on one side of the copper foam by chemical vapor deposition and the copper foam is directly used as an electrode after porous Pd@rGO cathode loading to the other side of the foam for the photo-assisted charging of the Li-ion oxygen battery. The amount of urea (CO(NH2)2), which is used as N atom source, is optimized to get maximum photo-anodic currents from the n-type graphene films. The optical band gap and the valance band edge potential of the optimized N-doped graphene film are determined as 2.00 eV and 3.71 VLi+/Li, respectively. X-ray photoelectron spectra provided that the atomic percent of N atoms in the graphene film is 1.34% and the graphitic, pyrrolic and pyridinic N atom percentages are 54.01%, 42.20% and 3.79%, respectively. The photo-assisted charging tests indicated that the N-doped graphene film photo-catalyst reduced the charging potential significantly even at 1000 mA g-1 (0.1 mA cm-2) current density and improved the cyclic discharge-charge performance of the Li-ion oxygen battery considerably. Nitrogen (N)-doped graphene film is synthesized as a photo-catalyst for the photo-assisted charging of the Li-ion oxygen battery. After structural and the optical characterizations, the effectiveness of the photo catalyst is determined by the charge/discharge tests that N-doped graphene film photo-catalyst reduced the charging potential and improved the cyclic performance of the Li-ion oxygen battery considerably.image
Keywords: chemical vapor deposition; Li-Ion oxygen batteries; N-doped graphene; photo-catalyst; photo-charging